PENGARUH INTERVENSI ENCHANCE RECOVERY AFTER SURGERY PADA POSTOPERATIVE TERHADAP LENGTH OF STAY: A SISTEMATIK REVIEW - Jaata, Jikrun (Coping: Community of Publishing in Nursing; Vol 9 No 1 (2021): Februari 2021DO - 10.24843/coping.2021.v09.i01.p14, 2021)
Background: Health problems arising in the post-operation must be addressed immediately to speed up the recovery process and minimize surgical complications thereby reducing the length of stay in hospital. Enhanced Recovery After Surgery (ERAS) interventions have been introduced to perioperative to reduce hospitalization days. Objective: this study aims to determine the effect of postoperative ERAS interventions on Length of Stay (LOS). Data Source: This systematic review was carried out in several international data bases published from 2010 to 2019 on Pubmed, Proquest, Google Scholar, and Science Direct which began searching on 01 to 31 July 2019. Method: a systematic review using the PRISMA checklist, then the research questions were arranged using PICO in the search for articles so that 11 articles met the inclusion criteria and then analyzed using CASP. Results: There were 7 out of 11 articles that had reviewed ERAS protocol interventions in the postoperative phase reducing the length of stay after the intervention was given and there were differences between the treatment group and the conventional group. While 4 articles were given early mobilization interventions which were part of ERAS in the postoperative phase there were 2 articles which after given the intervention also reduced the length of stay and the remaining 2 articles there was no difference in length of stay. However, the articles that have been reviewed are not known which items in the postoperative phase ERAS protocol cause a reduction in length of stay so that they become recommendations for research by looking at the effect of each item on the postoperative phase ERAS protocol. Conclusion: ERAS intervention in the postoperative phase reduces the length of stay. Keywords: laparotomy, abdominal surgery, colorectal surgery, ERAS, early mobilization, length of stay.